Health Determinants in the Incidence of Dengue Fever at Miraflores Health Center in Ecuador - Víctor A. Calero; Milka N. Mero; Elen M. Rodríguez; Juriko J. Choez; Ana del C. Ceruto; Mildredd Rebeka Soasty Vera (PT. Riset Press International, 2026)
Dengue is a viral disease transmitted by the Aedes aegypti mosquito, whose incidence constitutes a public health problem in tropical and subtropical regions. The objective of the study was to analyze the social determinants of health influencing the incidence of dengue in the community affiliated with the Miraflores Health Center in the canton of 24 de Mayo, Ecuador. A descriptive, explanatory, cross-sectional study using a quantitative approach was conducted from October 2024 to March 2025, with a sample of 60 residents selected through non-probabilistic sampling. Data were collected through structured surveys and direct observation and analyzed using descriptive statistics. The results showed that young adults, mostly women, were the most affected, presenting fever, headache, and myalgia as predominant symptoms. It was concluded that social determinants such as poor sanitation, persistent breeding sites, and domestic hygiene practices influence dengue transmission, highlighting the need for comprehensive and educational interventions in the community.